Artificial intelligence at work: The problem of managerial control from call centers to transport platforms - Woodcock, Jamie (Frontiers in Artificial Intelligence, 2022)
There has been much recent research on the topic of artificial intelligence at work, which is increasingly featuring in more types of work and across the labour process. Much research takes the application of artificial intelligence, in its various forms, as a break from the previous methods of organising work. Less is known about how these applications of artificial intelligence build upon previous forms of managerial control or are adapted in practice. This paper aims to situate the use of artificial intelligence by management within a longer history of control at work. In doing so, it seeks to draw out the novelty of the technology, while also critically appraising the impact of artificial intelligence as a managerial tool. The aim is to understand the contest at work over the introduction of these tools, taking call centres and transport platforms as case studies. Call centres are important because they have been a site of struggle over previous forms of electronic surveillance and computation control, providing important lessons for how artificial intelligence is, or may, be used in practice. In particular, this paper will draw out moments and tactics in algorithmic management has been challenged at work, using this as a discussion point for considering the possible future of artificial intelligence at work.